ANALISIS KOMUNIKASI ANTAR DEPARTEMEN FRONT OFFICE DAN HOUSEKEEPING DI SAPPHIRE BOUTIQUE HOTEL KUDUS - Ravita Sari; Enik Rahayu (LPSDI Bina Patria, 2025)
Interdepartmental work communication is a crucial factor in supporting smooth hotel operations and improving the quality of service to guests. This study aims to analyze the effectiveness of communication between the Front Office and Housekeeping departments at the Sapphire Boutique Hotel Kudus. The approach used is descriptive qualitative with data collection techniques in the form of in-depth interviews and observations of 13 staff from both departments. The results of the study showed that 61.5% of respondents considered interdepartmental communication to be quite effective, especially in routine activities such as the check-in process and laundry services. However, several obstacles were found such as delays in delivering information, differences in perception, and lack of written communication media. These obstacles risk reducing the speed and accuracy of service to guests. Solutions that have been implemented include daily briefings, the use of WhatsApp Group, and recording through log books. However, the effectiveness of communication is not optimal because there is no standard communication SOP and interdepartmental communication training. This study emphasizes the importance of strengthening a structured communication system, using appropriate media, and improving staff communication skills to support efficient work coordination and maximum guest service